The coast of the Levant, Byzantine- Fatimid conflict during the fourth and fifth centuries AH/ tenth eleventh centuries (358-447هـ/ 969-1055م) AD (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Levant  was always expressive of travelling to Egypt, through it over invaders and conquerors alike, so we find when all authorities and successive States in Egypt taken to extend their power and influence to the Levantine homes, whom the Fatimids, After Fatimids control Egypt, even started their campaigns to Levant to expand and ensure their security and stability, and that it did not cover over Levant interior but coastline featuring many important metropolises, Such as the cities of Sidon, Tripoli and Latakia and other vulnerable coastal centers, And that desire to expand into the Levant and it’s coast had her collision with the Byzantines and their wide influence at Levant and the Levantine coastline, Both of them had felt in the security stations its observers Levant coast guaranteed invasion again as if the internal influence any destabilization or scaling, Which they necessitated the military clash in a lot of times, As the influence of the parties on that coast was between highs and lows, and subject to many considerations including domestic situation and stability enjoyed by each other.